Optimalisasi Pelayanan Laundry: Perancangan dan Pengembangan Aplikasi Mobile Android Easy Wash - Metta Paramita; Yonky Pernando (STMIK Budi Darma, 2023)
The rapid advancements in technology have made it easy to access information, and various applications, including desktop, web, and mobile applications, have become an integral part of everyday life. Android-based smartphones are one of the most widely used devices, and applications are used not only for entertainment but also for business needs. Laundry service businesses are a common type of business, driven by the busy schedules of people, including workers and students. In the current pandemic situation, maintaining clothing hygiene is a priority. However, with the abundance of laundry services available, there is intense competition, and new consumers often struggle to find suitable laundry services. In this context, this research discusses an Android application called Easy Wash, which aims to help consumers find and book laundry services around them with the best quality. The application also allows consumers to track the process and estimate when their clothing will be ready. For laundry service owners, this is an opportunity to enhance their business. In this research, the Waterfall methodology is used in software development. The stages include analysis, design, coding, and testing. Use case diagrams are used to illustrate interactions between actors in the application. Class diagrams illustrate the database structure. Activity and sequence diagrams are used to depict the application flow. The application interface is also designed to meet consumer needs. The result of this research is the Easy Wash application, which can assist consumers in finding and booking laundry services easily and efficiently. The application has the potential to help laundry service owners increase their income, especially during the pandemic. The application is developed using Android Studio with the Java programming language. This abstract summarizes the entire research conducted in the development of the Android-based Easy Wash application